Heterogeneous gene expression signatures correspond to distinct lung pathologies and biomarkers of disease severity in idiopathic pulmonary fibrosis. Issue 1 (12th September 2014) - DePianto, Daryle J; Chandriani, Sanjay; Abbas, Alexander R; Jia, Guiquan; N'Diaye, Elsa N; Caplazi, Patrick; Kauder, Steven E; Biswas, Sabyasachi; Karnik, Satyajit K; Ha, Connie; Modrusan, Zora; Matthay, Michael A; et al.
Abstract : Background: There is microscopic spatial and temporal heterogeneity of pathological changes in idiopathic pulmonary fibrosis (IPF) lung tissue, which may relate to heterogeneity in pathophysiological mediators of disease and clinical progression. We assessed relationships between gene expression patterns, pathological features, and systemic biomarkers to identify biomarkers that reflect the aggregate disease burden in patients with IPF. Methods: Gene expression microarrays (N=40 IPF; 8 controls) and immunohistochemical analyses (N=22 IPF; 8 controls) of lung biopsies. Clinical characterisation and blood biomarker levels of MMP3 and CXCL13 in a separate cohort of patients with IPF (N=80). Results: 2940 genes were significantly differentially expressed between IPF and control samples (|fold change| >1.5, p<0.05). Two clusters of co-regulated genes related to bronchiolar epithelium or lymphoid aggregates exhibited substantial heterogeneity within the IPF population. Gene expression in bronchiolar and lymphoid clusters corresponded to the extent of bronchiolisation and lymphoid aggregates determined by immunohistochemistry in adjacent tissue sections. Elevated serum levels of MMP3, encoded in the bronchiolar cluster, and CXCL13, encoded in the lymphoid cluster, corresponded to disease severity and shortened survival time (p<10 −7 for MMP3 and p<10 −5 for CXCL13; Cox proportional hazards model). Conclusions: Microscopic pathological heterogeneity in IPF lung tissue corresponds to specific gene expression patterns related to bronchiolisation and lymphoid aggregates. MMP3 and CXCL13 are systemic biomarkers that reflect the aggregate burden of these pathological features across total lung tissue. These biomarkers may have clinical utility as prognostic and/or surrogate biomarkers of disease activity in interventional studies in IPF.